DINAMIKA POLITIK ANGGARAN DALAM PENYUSUNAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) TERKAIT PERBAIKAN KERUSAKAN JALAN DI KABUPATEN INDRAGIRI HULU TAHUN 2023 - Devanda, Noval; Susanto, Agus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study discusses the dynamics of budget politics in the process of preparing the 2023 Indragiri Hulu Regency Regional Revenue and Expenditure Budget (APBD), especially regarding the budget allocation for repairing damaged roads. The budget is a crucial aspect in local government policy, where its formulation involves various political interests. This study aims to analyze the budget politics process involving the executive and legislative in determining budget priorities, as well as the obstacles faced in implementing road infrastructure repair policies. This study uses a qualitative approach with a descriptive method. Data were obtained through interviews with related parties, such as members of the Regional People's Representative Council (DPRD), the Public Works and Spatial Planning Agency (PUPR), and analysis of policy documents. The results of the study show that budget constraints are the main challenge in realizing road repairs, where the funds allocated of IDR 51.9 billion are still far from the ideal need of IDR 297.8 billion. In addition, the political dynamics in discussing the APBD involve negotiations between the local government and the DPRD, which are often influenced by political interests and other development priorities. The conclusion of this study confirms that the budget politics process in road repairs in Indragiri Hulu Regency is influenced by factors of budget limitations, local government priority scales, and political interests in decision making. It is hoped that there will be increased transparency, efficiency, and effectiveness in budget management to ensure more optimal infrastructure repairs. Keywords: Budget Politics, APBD, Infrastructure, Road Repairs, Indragiri Hulu Regency